Nonlinear decay of Langmuir waves into counter-propagating surface ones - Akimov, Yu.A.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2006)
This paper presents a study of the nonlinear excitation of surface waves involving a Langmuir wave decay at a
plasma-dielectric interface. The Langmuir wave is considered to be incident perpendicularly upon the interface, where it
decays into a couple of counter-propagating surface ones. The excitation is analyzed for both the undamped and damped
Langmuir waves. Исследовано нелинейное возбуждение двух встречных поверхностных волн при распаде ленгмюровской волны, падающей перпендикулярно на границу раздела плазма-диэлектрик. Проанализирована динамика возбуждения поверхностных волн незатухающей и затухающей ленгмюровскими волнами. Дослiджено нелiнiйне збудження двох зустрiчних поверхневих хвиль при розпадi ленгмюрiвської хвилi, що
падає перпендикулярно на межу розподiлу плазма-дiелектрик. Проаналiзована динамiка збудження поверхневих
хвиль незагасаючою та загасаючою ленгмюрiвськими хвилями.